2018
DOI: 10.1590/0074-02760170217
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal compounds of Nectria pseudotrichia, an endophytic fungus isolated from the plant Caesalpinia echinata (Brazilwood)

Abstract: BACKGROUNDIn a screen of extracts from plants and fungi to detect antileishmanial activity, we found that the ethyl acetate extract of the fungus Nectria pseudotrichia, isolated from the tree Caesalpinia echinata (Brazilwood), is a promising source of bioactive compounds.OBJECTIVESThe aims of this study were to isolate and determine the chemical structures of the compounds responsible for the antileishmanial activity of the organic extract from N. pseudotrichia.METHODSCompounds were isolated by chromatographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Therefore, contributing studies that may lead to the discovery of a compound or compounds with anti-leishmaniasis activity is of great importance for the control of these diseases. Similar works tested endophytic fungi isolated from plants from different Brazilian biomes, and they obtained leishmanicides that exhibited promise against other species of Leishmania that cause integumentary leishmaniasis, which is less deadly than visceral leishmaniasis (VL) (Marinho et al, 2005;Campos et al, 2008;Rosa et al, 2010;Brissow et al, 2017;Cota et al, 2018). Little is known about the anti-leishmaniasis activity of these isolates against the species that cause VL (Leishmania donovani and L. infantum chagasi).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, contributing studies that may lead to the discovery of a compound or compounds with anti-leishmaniasis activity is of great importance for the control of these diseases. Similar works tested endophytic fungi isolated from plants from different Brazilian biomes, and they obtained leishmanicides that exhibited promise against other species of Leishmania that cause integumentary leishmaniasis, which is less deadly than visceral leishmaniasis (VL) (Marinho et al, 2005;Campos et al, 2008;Rosa et al, 2010;Brissow et al, 2017;Cota et al, 2018). Little is known about the anti-leishmaniasis activity of these isolates against the species that cause VL (Leishmania donovani and L. infantum chagasi).…”
Section: Discussionmentioning
confidence: 99%
“…However, this leishmaniasis is the least severe and lethal. A number of studies have demonstrated activities against this type of leishmaniasis (Santiago et al, 2011;Cota et al, 2018). To date, there have been no studies investigating the role played by related endophytic fungi from mangroves in producing secondary metabolites with leishmanicidal activity against L. infantum chagasi.…”
Section: Introductionmentioning
confidence: 99%
“…Endo-phytic fungi are the major contributor to most of the natural products produced by endophytic microorganisms 9 . The natural products produced by endophytic fungi have potential applications in the development of antimicrobial, antiviral 10 , antileishmanial 11 , anti-oxidant, anticancer, antiparasitic, and bio-control agents 12 .…”
Section: Ijpsr (2020) Volume 11 Issue 11 (Research Article)mentioning
confidence: 99%
“…These compounds active in the micromolar range are also small molecules, ideal for further optimization through medicinal chemistry. Recently, in a preliminary screening to search potential antileishmanial compounds, Cota et al [34] identified ethyl acetate extract of the fungus Nectria pseudotrichia, an endophyte of Caesalpinia echinata as promising against Leishmania braziliensis. The fractionation led to seven compounds including 10-acetyl trichoderonic acid A (21), 6′-acetoxy-piliformic acid (22), 5′,6′-dehydropiliformic acid (23), piliformic acid (24), hydroheptelidic acid (25), xylaric acid D (26), and cytochalasin D (27) [36].…”
Section: Antileishmanial Metabolites Produced By Endophytesmentioning
confidence: 99%